The use of ultrasound contrast to evaluation the effectiveness of superselective embolization of arteries prostate of benign hyperplasia - O. B. Zhukov (Andrologiâ i Genitalʹnaâ Hirurgiâ, 2015)
The article presents the first Russian and international experience in the application of ultrasound contrast to evaluation the effectiveness of superselective embolization of arteries prostate benign hyperplasia her. Thoroughly describes the methodology of the arteries embolization prostate hyperplasia her. Given a clear algorithm and the necessary tools in this type of operations. Presented rationale for the use of microspheres Embozene as the most innovative embolization material. These microspheres exhibit shape memory, which allows them to shrink to 35 % and immediately recover its original volume after the release of the microcatheter. Studies have shown that the microspheres Embozene retain its original volume is not fragmented, which is a very important fact for the target artery embolization and radical prostate. Attentive readership presents the rationale and mechanical properties of ultrasound contrast, which is only selectively within the lumen of blood vessels and eliminates early relapse of prostate adenoma after embolization her arteries in its application. This area will allow the use of ultrasound contrast followed by researchers to determine the nature of the blood supply to the prostate and its changes after embolization of the arteries of the prostate. The article presents the clinical and uroflowmetry results of patients who underwent embolization. Denotes the vector of this technology in the elimination of the continued growth of the local and local recurrence of prostate cancer.